Polypedilum (Cerobregma) heberti sp. n. (Diptera: Chironomidae) from Gaoligong Mountains, Yunnan, China - Lin, Xiao-Long; Yu, Hai-Jun; Zhang, Rui-Lei; Wang, Xin-Hua (Zootaxa, 2019)
DNA barcodes and morphology recognize a new non-biting midge within the genus Polypedilum (Diptera: Chironomidae). Polypedilum (Cerobregma) heberti Lin et Wang sp. n. is described and illustrated based on an adult male from Gaoligong Mountains, Yunnan, China. Key to adult males of the subgenus Cerobregma is given.